Expanding the social media presence of the Journal of Neurointerventional Surgery: editor's report. (29th February 2016) - Fargen, Kyle M; Ducruet, Andrew F; Hyer, Madison; Hirsch, Joshua A; Tarr, Robert W
Abstract : The use of social media is pervasive throughout society and serves many purposes. Traditional forms of advertising are being upended as vendors recognize the unique abilities of social media platforms to target their messages to specific customers. Peer reviewed medical and professional journals are beginning to develop their own initiatives using social media to advertize unique content. We present the nascent Journal of NeuroInterventional Surgery experience.